Ablation of the great saphenous vein with F-care versus Closurefast endovenous radiofrequency therapy: Double-blinded prospective study. (September 2020) - Bitargil, Macit; Kılıç, Helin E
Objectives: F-care (endovenous radiofrequency, F Care Systems, Antwerp, Belgium) is a relatively new radiofrequency ablation technique for the treatment of venous insufficiency. There is a lack of published data about F-care in literature. This study aimed to prospectively compare the F-care method with conventional endovenous radiofrequency ablation Closurefast method for the management of incompetent great saphenous veins. Methods: Between June 2015 and December 2018, 114 patients with incompetent varicose veins were treated either with the F-care or Closurefast. The pre-, intra-, postprocedural, and follow-up data of the patients were collected and prospectively compared. Results: The average ablated vein length was 23.1 ± 4 cm in the F-care group and 26.6 ± 4 cm in the Closurefast group ( P  =   0.01). The average procedure time was 17.4 ± 4 min (range: 10–30 min) in the F-care group, and 17.1 ± 3 min (range: 11–27 min) in the Closurefast group ( P  =   0.77). The one-month total occlusion rates in the F-care and Closurefast groups were 96.2% and 98.1%, respectively ( P  =   0.5). The one-year full occlusion rates in the F-care and Closurefast groups were 71.7% and 90.6%, respectively ( P  =   0.013). In both the F-care and Closurefast groups, the venous clinical severity scores declined significantly with no difference between groups. There was no significant difference between adverse events following F-care treatment compared with Closurefast treatment ( P  ≤   0.05). Conclusions: The F-care system was as safe and fast, but the one-year closure rate was significantly lower when compared to the other method. There was no significant difference between the adverse effects of both approaches. Further large-scale, multi-center prospective studies with long-term outcomes are required to identify the effectiveness of F-care treatment modality for patients with saphenous vein insufficiency.